A prospective study on the neurological complications of breast cancer and its treatment: Updated analysis three years after cancer diagnosis. (October 2016) - Fontes, Filipa; Pereira, Susana; Castro-Lopes, José Manuel; Lunet, Nuno
Abstract: Objectives: To quantify the prevalence of neurological complications among breast cancer patients at one and three years after diagnosis, and to identify factors associated with neuropathic pain (NP) and chemotherapy-induced peripheral neuropathy (CIPN). Material and methods: Prospective cohort study including 475 patients with newly diagnosed breast cancer, recruited among those proposed for surgical treatment (Portuguese Institute of Oncology, Porto). Patients underwent a neurological evaluation and had their cognitive function assesses with the Montreal Cognitive Assessment, before treatment and at one and three years after enrollment. We estimated the prevalence of each neurological complication, and odds ratios (OR), adjusted for socio-demographic and clinical characteristics, to identify factors associated with NP and CIPN. Results: More than half of the patients [54.7%, 95% confidence interval (95%CI): 50.2–59.2] presented at least one neurological complication, at one or at three years after cancer diagnosis. Between the first and the third year of follow-up, there was an increase in the prevalence of NP (from 21.1% to 23.6%), cognitive impairment (from 7.2% to 8.2%), cerebrovascular disease (from 0.6% to 1.5%) and brain metastasis (from 0.0% to 0.6%). The prevalence of CIPN decreased from 14.1% to 12.6%. Axillary lymph node dissection was associated with NP at one year (OR = 2.75, 95%CI: 1.34–5.63) and chemotherapy with NP at three years (OR = 2.10, 95%CI: 1.20–3.67). Taxane-based chemotherapy was strongly associated with prevalence of CIPN at one and three years. Conclusion: Neurological complications are frequent even three years after cancer diagnosis and NP remained the major contributor to the burden of these conditions among survivors. Highlights: Neurological complications are frequent even three years after cancer diagnosis. NP was the most frequent at one and three years after cancer diagnosis. Axillary lymph node dissection was associated with higher odds of NP at one year. Chemotherapy was associated with higher odds of NP at three years. Taxane-based chemotherapy was associated with higher odds of CIPN.